Spread of fire blight in Austria and Hungary - variability of Erwinia amylovora strains - M. Keck; M. Hevesi; W. Ruppitsch; A. Stöger; S. Richter (Plant Protection Science, 2002)
First outbreaks of fire blight were detected in Austria in 1993 and in Hungary in 1995. 137 Erwinia amylovora isolates were compared by PCR-RFLP, sequencing of the repeat region of the PstI fragment of plasmid pEA29, RAPD and AFLP analysis. Differences of repeat numbers in first isolates were observed. Six isolates showed different RAPD profiles. In AFLP analysis, so far, no differences in fragment pattern were determined. Pathogenicity tests with micropropagated apple cultivars revealed differences in plant susceptibility and in virulence of isolates. Responses of Malus tissue were visualized by the use of epifluorescence microscopy through the localization and the production of substances involved in cellular defence mechanisms (e.g. flavonoids, lignin) in various susceptible cultivars. The effect of bacterial strains differing in pathogenicity is shown by cellular peroxidase and flavonoid production.